Favorable Growth Hormone Treatment Response in a Young Boy with Achondroplasia - Marina Krstevska-Konstantinova; Ana Stamatova; Zoran Gucev (Academy of Medical Sciences of Bosnia and Herzegovina, 2016)
Background: Achondroplasia is a skeletal dysplasia, the most common cause of rhizomelic dwarfism. Case presentation: This is a ten year old boy who was first diagnosed prenatally. He had a mutation c1138G>A in the gene FGFR3 in a heterozygotic constellation. His IGF1 and IGFBP3 levels were normal. Two stimulation tests for growth hormone were performed with values within the reference range. His psychomotor development was adequate for his age except for speech difficulty. He started with recombinant hGH (r-hGH) at the age of 3.4 years in a dose of 0.06 mg/kg. His mean Height SDS (HtSDS) was -2.2. Results: The growth increased to 10 cm/year in the first year of therapy (HtSDS -1.1). It decreased during the second year to 4 cm (HtSDS -1.7) and again increased during the third year to 8 cm/year (HtSDS–1.3). In the next years the growth was constant (6.5, 2.3, 3.5 cm / year). He is still growing in the 3rd percentile of the growth curve (HtSDS – 1.2) under GH treatment. The body disproportion remained the same. Conclusion: The growth response on GH treatment was satisfactory in the first 4 years of treatment, and the boy still continued to grow. The young age at the start of treatment was also of importance. Our other patients with achondroplasia who started treatment older had a poor response to growth hormone.
Keywords: achondroplasia; skeletal dysplasia; growth hormone treatment